2017
DOI: 10.3390/ma10111232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling Time on the Microstructure, Physical and Mechanical Properties of Al-Al2O3 Nanocomposite Synthesized by Ball Milling and Powder Metallurgy

Abstract: The effect of milling time on the morphology, microstructure, physical and mechanical properties of pure Al-5 wt % Al2O3 (Al-5Al2O3) has been investigated. Al-5Al2O3 nanocomposites were fabricated using ball milling in a powder metallurgy route. The increase in the milling time resulted in the homogenous dispersion of 5 wt % Al2O3 nanoparticles, the reduction of particle clustering, and the reduction of distances between the composite particles. The significant grain refining during milling was revealed which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 36 publications
5
50
0
2
Order By: Relevance
“…The leaching percentages of alumina and silica were 50% and 30%, respectively, and were rather constant, irrespective of the ball milling time. Table 2 shows that average crystallite size decreased rapidly from 52.6 to 45.0 nm as milling time increased to 5 h, but the decrease in crystallite size was diminished with the further increase in milling time from 5 to 10 h. The variation in the crystallite size together with the change in morphology of the mechanically activated dross with milling time agrees well with the leaching data shown in Figure 3 [20].…”
Section: The Effect Of Milling Time and Speedsupporting
confidence: 81%
“…The leaching percentages of alumina and silica were 50% and 30%, respectively, and were rather constant, irrespective of the ball milling time. Table 2 shows that average crystallite size decreased rapidly from 52.6 to 45.0 nm as milling time increased to 5 h, but the decrease in crystallite size was diminished with the further increase in milling time from 5 to 10 h. The variation in the crystallite size together with the change in morphology of the mechanically activated dross with milling time agrees well with the leaching data shown in Figure 3 [20].…”
Section: The Effect Of Milling Time and Speedsupporting
confidence: 81%
“…We attribute this increase to the lattice distortion induced by plastic deformation. This effect has been also found for other metals such as Cu and Al, for example. We also note that solid solution formation could affect the lattice parameters.…”
Section: Resultssupporting
confidence: 59%
“…And the structural evolution of metallic glasses generally shows a monotonous tendency (relaxation or rejuvenation) along with the milling time, the observation intervals of which is at least half an hour [4,6,7,15]. There comes a question that whether this monotonicity just an observation result under a long observation interval, since an exception was found that crystallization and rejuvenation appear alternately in Zr 66.7 Cu 33.3 metallic glass during the milling process [16].…”
Section: Introductionmentioning
confidence: 99%